Man Without Qualities - Robert Musil; MUSIL (Robert); WILKINS (Sophie) Tr; PIKE (Burton) Ed (USA Alfred A Knopf Inc., 1995)
Set in Vienna on the eve of World War I, this great novel of ideas tells the story of Ulrich, ex-soldier and scientist, seducer and skeptic, who finds himself drafted into the grandiose plans for the 70th jubilee of the Emperor Franz Josef. This new translation$1 (Bpublished in two elegant volumes$1 (Bis the first to present Musil's complete text, including material that remained unpublished during his lifetime.s
Keywords: German Fiction Tr in English; German Literature